2021
DOI: 10.1016/j.matt.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Robust Mesoporous Zr-MOF with Pd Nanoparticles for Formic-Acid-Based Chemical Hydrogen Storage

Abstract: Formic acid is a compelling chemical storage platform for hydrogen gas but the lack of an efficient dehydrogenation catalyst is preventing its commercial use. In this issue of Matter, Wang et al. reports a fine-tuned zirconium metal-organic-framework with palladium nanoparticles that effectively dehydrogenates formic acid without degradation.Mesoporosity in solid structures with pores between the diameters of 2~50 nm offers diverse applications including adsorption, catalysis, energy storage and conversion. 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, the resultant MOF‐HGCCs with intrinsic pristine MOFs’ merits and implemented additional properties provide a brand‐new avenue to realize the significantly boosted catalytic activities, selectivity, and stability for highly efficient MOF electrocatalysis, where the pristine MOFs and introduced/foreign materials are hosts and guests, respectively. [ 58 ] By dividing MOF‐HGCCs into two groups according to whether they contain precious metals or not, their recent advancements related to the design, structure–performance relationship exploration, and practical application are systematically and clearly summarized in the following two subsections.…”
Section: Mof‐based Host–guest Composites For Electrocatalysismentioning
confidence: 99%
“…Therefore, the resultant MOF‐HGCCs with intrinsic pristine MOFs’ merits and implemented additional properties provide a brand‐new avenue to realize the significantly boosted catalytic activities, selectivity, and stability for highly efficient MOF electrocatalysis, where the pristine MOFs and introduced/foreign materials are hosts and guests, respectively. [ 58 ] By dividing MOF‐HGCCs into two groups according to whether they contain precious metals or not, their recent advancements related to the design, structure–performance relationship exploration, and practical application are systematically and clearly summarized in the following two subsections.…”
Section: Mof‐based Host–guest Composites For Electrocatalysismentioning
confidence: 99%
“…So far, many MOF-loaded Pd-based catalysts are evolved in FA decomposition reaction. A main advantage of these porous framework materials is that the functional groups like amine groups could be directly incorporated using an NH 2 -containing ligand for the synthesis of MOFs, thus leading to the uniform distribution of the basic groups throughout the whole MOF materials . For instance, using NH 2 -MIL-101 as a carrier, Gao obtained a highly active supported PdCr alloy NP catalyst for additive-free FA dehydrogenation, giving a high TOF value of 2009 h –1 at 323 K .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using NH 2 -MIL-101 as a carrier, Gao obtained a highly active supported PdCr alloy NP catalyst for additive-free FA dehydrogenation, giving a high TOF value of 2009 h –1 at 323 K . Lately, NH 2 -MIL-101-supported PdNi and PdAg NP catalysts have also been prepared by an impregnation–reduction method and showed relatively excellent activity and stability for FA decomposition. , More significantly, the structurally stable Zr-MOFs (such as UiO-66 and its derivatives) may bring some new chances for constructing Pd-based catalysts with better performance. According to the literature reported by Wang et al ., they prepared NH 2 -containing UiO-66 immobilized PdAg alloy NPs and found that the resultant Ag 1 Pd 4 @NH 2 -UiO-66 catalyst expressed a decent activity (TOF = 525 h –1 ) at 323 K and possessed higher durability for FA decomposition reaction .…”
Section: Introductionmentioning
confidence: 99%